ANALISIS PERBANDINGAN PENGGUNAAN APLIKASI PENGOLAH KATA MICROSOFT WORD DAN OOW BERDASARKAN SERVQUAL - Devia Titania; Asrul Huda (Universitas Negeri Padang, 2019)
This research was motivated by problems because paid software as OpenOffice Writer and Abi Word are free software, MS Office and OpenOffice Writer have many similarities in word processing. The purpose of this research was to analyze the Microsoft word software and open office writer in its operation in terms of features, usage security, user interface and rights. This type of research was descriptive which is correlational. The population in this study were users of word processing software in 2015 Informatics and Computer Education Students as many as 69 people. The number of samples was 40 people. Research results show that 1) Usability Variables, Information Quality and Interaction Quality together have a significant effect of 80% on the level of service quality of word processing application users, 2) variable X was very influential on user satisfaction of word processing applications and 3) simultaneously (F test) can provide information that Usability, Information Quality and Interaction Quality from the application together must be considered to improve the word processing application service. Keywords: Comparison of Word Processing Applications, Microsoft Word and Open Office Writter